Communicating with children and adolescents : action for change - Bannister, Anne; Huntington, Annie, 1962- (Jessica Kingsley Publishers, 2002)
At a time when expectations and assumptions about the delivery of services to children and adolescents are being reconfigured - for example, around the rights of children and adolescents as young citizens - adults are seeking to ensure that they deliver services in creative and empowering ways, ensuring that the opinions of young people are actively solicited and encouraged. Action methods - communication methods using the body as well as speech - provide non-threatening ways of communicating which can be understood by children of all ages and from many cultures. This book places action method.